INVESTIGATION OF THE EFFECTIVENESS OF USING SELF-DETERMINATION THEORY IN TEACHING BIOLOGY FOR GRADE TEN STUDENTS - Menike, H.P.R.; Chandrasena, W.D. (International Journal of Research -GRANTHAALAYAH, 2019)
Biology is a very important discipline as it focusses on structure and functions of living organisms in this world. Hence, it has become a significant area of study in school curriculum and it is also a main subject discipline in the Grade 10 science syllabus in Sri Lanka. The time allocated for the biology section in Grade 10 syllabus is one third of the total time. Although, biology is perceived as an easy discipline to study compared to other disciplines in science, students’ achievement in biology is not very satisfactory. Thus, there may be different reasons for students’ poor achievement in biology such as content in the syllabus, teaching style, students’ learning and studying habits, students’ negative feeling and attitudes towards the topics, and lack of enough resources (Cimer, 2011). The practices based on Self-Determination Theory (SDT) could be used in biology classrooms to enhance students’ enthusiasm towards learning. SDT is an important psychological theory of motivation and it addresses issues of extrinsic and intrinsic motivation. According to SDT people have three innate psychological needs: competence, relatedness, and autonomy. If these universal needs are met, the theory argues that people will function and grow optimally. Thus, to actualize their inherent potential, the social environment needs to nurture these needs (Deci & Ryan, 2014). However, there is a dearth of research and practices in Sri Lankan school classrooms using SDT to facilitate students’ learning. Hence, the unit of “Classification of Organisms” in Grade 10 syllabus was selected to study the effectiveness of SDT in teaching biology for Grade 10 students. “Classification of Organisms” is an important unit since it is the foundation of learning about different types of living beings. This is an experimental study and two groups of students were used as control and experimental. Experimental group is taught using the SDT and the control group is taught according to the traditional method. During the lessons observations were made while maintain the records of field notes. The collected data were analysed using thematic analysis. Students’ motivation, engagement, enthusiasm, and performance in both groups were compared. The results of the study showed that the above characteristics are higher in the experimental group compared to the control group. Thus, the classroom practices based on the SDT can be used as a good technique in teaching biology in order to enhance the students’ intrinsic motivation.